Evaluation of 30 Day Readmissions After Index Ventricular Assist Device Implantation in the United States. Issue 6 (August 2019) - Setareh-Shenas, Saman; Thomas, Felix; Cole, Robert M.; Lemor, Alejandro; Herzog, Eyal; Arabia, Francisco; Moriguchi, Jaime
Abstract : Ventricular assist device (VAD) implantation has improved quality of life and short-term survival for advanced heart failure patients. There are limited data from single-center studies addressing the characteristics and etiologies of 30 day readmissions after VAD implant. We used the Nationwide Readmissions Database (NRD) 2014 to identify insertion of implantable heart assist system during index admission. Primary and secondary outcomes were 30 day readmissions and leading etiologies, respectively. We analyzed 1, 481 patients who received VAD during the primary admission of whom 1, 315 patients survived to hospital discharge (mortality rate 11.2%), and 60.6% were discharged to a nursing facility. One hundred and thirty-one (10.0%) patients were readmitted within 30 days of primary hospitalization. Leading etiologies of 30 day readmission were bleeding (24%), heart failure (18%), and device complications (14%). Mean length of stay during readmission was 13.8 days with a mortality rate of 2.1%. Fifty percent of 30 day readmissions were readmitted from day 22 to 30. Variables for predictors of 30 day readmissions were not statistically significant. By identifying gastrointestinal bleeding, heart failure, and device complications as leading etiologies of 30 day readmission post-VAD implantation, providers can potentially modify practices to prevent hospital readmissions, decreasing cost of care, and improving the quality of life of patients.